Pressure-induced phase transitions in single-crystalline Cu4Bi4S9 nanoribbons - 胡靖宇 李劲 张思佳 赵豪飞 张庆华 姚湲 赵清 石丽洁 邹炳锁 李延春 李晓东 刘景 朱恪 刘玉龙 靳常青 禹日成 (中国物理B：英文版, 2013)
In situ angle dispersive synchrotron X-ray diffraction and Raman scattering measurements under pressure are em- ployed to study the structural evolution of Cu4Bi4S9 nanoribbons, which are fabricated by using a facile solvothermal method. Both experiments show that a structural phase transition occurs near 14.5 GPa, and there is a pressure-induced re- versible amorphization at about 25.6 GPa. The electrical transport property of a single Cu4Bi4S9 nanoribbon under different pressures is also investigated.